Regime change and foreign policy: Portugal, Indonesia and the fate of East Timor - Gorjão, Paulo (2005)
This article focuses on the impact of regime change on changes in foreign policy. More specifically, it addresses (a) the issue of legitimacy (or otherwise) of a given policy and (b) individual and collective assessments and strategies of those involved. As a case study, this article deals with Portugal, Indonesia and East Timor.